Media Smart Box Inovatif Meningkatkan Hasil Belajar Pelajaran PPKN Kelas III Sekolah Dasar - Humairoh, Fakhriah; Sri Sami Asih (Jurnal Pendidikan dan Pengajaran, 2024)
In learning, students tend to be passive because teachers do not develop innovative media, so learning outcomes are low. This study aims to develop innovative, intelligent box media in the PPKn lesson content on the image's meaning of the state symbol of Garuda Pancasila. This type of research is research and development (R&D) with the Borgh and Gall model. The subjects of this study were 1 learning material expert, 1 learning media expert and 1 teacher. The population in this study was 30 as the research population. The data collection methods were observation, interviews, questionnaires, and tests. The research instruments used were multiple choice. The data analysis technique in this study used quantitative data analysis and inferential statistics. The results showed that the innovative smart box media received a feasible category from media and material validation experts. Based on the results of the paired sample t-test on a large and small scale, there was a significant difference after using the innovative smart box media. Based on the results of the N-gain test on both a small and large scale, there was an increase in values ​​between the pretest and posttest. It can be concluded that innovative smart box learning media effectively improves student learning outcomes in the PPKn subject. The research implies that the innovative smart box media developed suits PPKn learning.